Emergence and spread of VIM-type metallo-β-lactamase-producing Pseudomonas aeruginosa clinical isolates in Japan. (December 2020) - Hishinuma, Tomomi; Uchida, Hiroki; Tohya, Mari; Shimojima, Masahiro; Tada, Tatsuya; Kirikae, Teruo
Highlights: VIM-producing P. aeruginosa increased between 2012 and 2018 in hospitals in Japan. The isolates produced VIM-1, VIM-2, VIM-24, VIM-60 or a novel variant VIM-66. The isolates belonged to ST179, ST233, ST235 or ST1816. The ST1816 isolates produced VIM-24, VIM-60 and VIM-66 with Arg228Leu. Abstract: Objectives: The aim of this study was to determine the genetic and epidemiological properties of Pseudomonas aeruginosa strains producing VIM-type metallo-β-lactamases isolated from patients in Japan. Methods: A total of 1860 clinical isolates of carbapenem-resistant P. aeruginosa were obtained from patients hospitalised in Japan from 2012–2018. Carbapenem-resistant P. aeruginosa isolates were screened for bla VIM genes by PCR. Antimicrobial susceptibility was determined by the broth microdilution method. The whole genomes of these isolates were sequenced using a next-generation sequencer, and phylogenetic analysis was performed using single nucleotide polymorphism concatemers. Multilocus sequence typing (MLST) was performed and drug resistance genes were identified using whole-genome sequence data. Results: Of 1860 isolates, 25 bla VIM -positive isolates were screened in nine medical settings in Japan. The population of VIM-producing P. aeruginosa significantly increased between 2012 and 2018. All 25 bla VIM -positive isolates were resistant to imipenem, meropenem and ciprofloxacin but were susceptible to colistin. The isolates harboured bla VIM-1, bla VIM-2, bla VIM-24, bla VIM-60 or the novel variant bla VIM-66 and belonged to four different sequence types (STs), including ST179, ST233, ST235 and ST1816. The 11 isolates harbouring bla VIM-24, bla VIM-60 or bla VIM-66 were obtained from a single hospital, all belonging to ST1816. VIM-24, VIM-60 and VIM-66 had an amino acid substitution (Arg228Leu) compared with VIM-2. Conclusions: The number of P. aeruginosa strains producing VIM-type MBLs has increased in medical settings in Japan. Pseudomonas aeruginosa ST1816 producing VIM enzymes with Arg228Leu substitution have emerged and evolved in a medical setting in Japan.